An integrated genomic regulatory network of virulence-related transcriptional factors in Pseudomonas aeruginosa - Hao Huang (Nature Portfolio, 2019)
The virulence of Pseudomonas aeruginosa is regulated by many transcriptional factors (TFs). Here, the authors study the crosstalk between 20 key virulence-related TFs, validate 347 functional target genes, and describe the regulatory relationships of the 20 TFs with their targets in a network that is available as an online platform.